Symmetric Resonance Mechanism for Elimination of Parasitic Torque of a Permanent Magnet Generator under Stable Load - K. V. Dobrego; I. A. Koznacheev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Vibration and torque ripple of the permanent magnet generator axis cause excessive wearing up of the generator, noise, efficiency reduction. The article theoretically considers the possibility of eliminating the oscillation of the rotation torque of the permanent magnets generator at constant load due to mutual compensation of the interaction of coils with the field of permanent magnets in the case of certain symmetry of this field. This effect is called pi resonance. For a given class of model functions of the magnetic field density of permanent magnets, it is shown that full compensation occurs with a certain number of coils (Ns) and magnets (Nr), while for other combinations of {Ns, Nr} the interaction is in the nature of oscillations. Pi resonance tables are given for a number of model field density functions represented by Fourier series up to the fifth power. Pi resonance is primarily realized in the case of a small difference in the values of Nr and Ns, which corresponds to the location near the main diagonal of the pi resonance table, as well as at the values of Nr, Ns corresponding to prime numbers. The number of configurations {Nr, Ns} providing pi resonance (compensation of parasitic torques) is the largest for the sinusoidal magnetic flux density and decreases if the magnetic flux density function is approximated by a high-degree Fourier series. It is shown that in the absence of coil cores, pi resonance is possible at Nr = Ns. An additional possibility of pi resonance is shown when placing coils on opposite sides of the rotor. A simplified method of investigating the system (without integrating the equation for the induction current) is substantiated. The results can be used in the design of permanent magnets generators and motors.